Foot and Ankle Characteristics Associated With Falls and Falls Risk in Adults With Rheumatoid Arthritis - Brenton-Rule, Angela Robyn (Auckland University of Technology, 2015)
The thesis investigated whether foot and ankle characteristics are associated with falls or falls risk in adults with rheumatoid arthritis (RA). A systematic review of the incidence and risk factors for falls in people with RA found inconsistency in methods for collecting falls data and conflicting evidence about fall risk factors. The current study sought to extend our understanding of fall risk in people with RA through the inclusion of foot and ankle characteristics. The thesis consisted of a cross-sectional study followed by a 12-month prospective study of 201 adults with established RA. In the cross-sectional study, falls experienced in the preceding year were recorded (12-month fall history) and a range of clinical and foot and ankle characteristics were measured. Participants were then followed for 12 months to record the occurrence of prospective falls following the Prevention of Falls Network Europe (ProFaNE) consensus guidelines for falls research. Data analysis involved both univariate and multivariate analysis. Falls incidence for the cross-sectional study was 59%. The logistic regression analysis, controlling for age, identified (a) clinical and foot and ankle characteristics which were independently associated with falls in the preceding 12 months; and (b) clinical and foot and ankle characteristics that were independent predictors of prospective falls. Clinical and foot and ankle characteristics that were independently associated with falls in the preceding 12 months included cardiovascular disease (odds ratio (OR) 3.22, P=0.024), midfoot peak plantar pressure (OR 1.12 [for each 20 kPa increase], P=0.046) and foot-related disability and impairment (OR 1.17 [for each 3 point increase], P=0.005). Falls incidence for the 12-month prospective study was 42%. Clinical and foot and ankle characteristics found to be independent predictors of prospective falls (not controlling for 12-month fall history) included psychotropic medication (OR 2.35, P=0.025) and presence of foot or ankle tender joints (OR 1.95, P=0.034). When 12-month fall history was included in the analysis, psychotropic medication (OR 2.34, P=0.025) and 12-month fall history (OR 2.27, P=0.008) were independent predictors of falls. Falls are complex, multi-system events with multifactorial aetiologies. Therefore, no single risk factor can be identified as the cause of any given fall event. As such, the thesis presented a synthesis of the findings relating to the foot and ankle fall risk factors, with a hypothetical model on how these risk factors might be interrelated. Further work is required to test the hypotheses relating to interrelationships between foot and ankle fall risk factors. Clinical implications included a number of assessments that could be incorporated into routine clinical practice to identify or monitor fall risk in people with established RA. Future work is needed to confirm the study findings in people with early RA and to develop a tool to screen for falls risk, and predict falls, in people with RA. Future research could include dynamic tests of balance, 3D gait analysis of lower limb and foot function and assessment of lower leg muscle strength and ankle joint proprioception. In addition, further evaluation of the role of footwear in falls, in people with RA, is warranted. Qualitative research, exploring perceptions around falls and falls risk, and the development of expert consensus guidelines for participant grouping in falls data analysis, would benefit future RA falls research.
Keywords: Rheumatoid arthritis; Falls; Fall risk factors; Feet; Balance; Disability; Impairment